The Stillbirth Collaborative Research Network Postmortem Examination Protocol - Pinar, Halit; Koch, Matthew A.; Hawkins, Hal; Heim-Hall, Josefine; Abramowsky, Carlos R.; Thorsten, Vanessa R.; Carpenter, Marshall W.; Zhou, Hong Holly; Reddy, Uma M. (American Journal of Perinatology, 2012)
After reviewing the state of knowledge about the scope and causes of stillbirth (SB) in a special workshop sponsored by the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD), the participants determined that there is little guidance regarding the best use of postmortem examination (PM) to address the pathogenesis of stillbirth. In this report, we describe the PM procedure designed and used in the NICHD-supported Stillbirth Cooperative Research Network (SCRN). Perinatal pathologists, clinicians, epidemiologists, and biostatisticians at four tertiary care centers, a data coordinating center, and NICHD developed a standardized approach to perinatal PM, which was applied to a population-based study of stillbirth as part of the SCRN. The SCRN PM protocol was successfully instituted and used at the four medical centers. A total of 663 women with stillbirth were included: 620 delivered a single stillborn infant, 42 delivered twins, and one delivered triplets for a total of 676 stillborn infants. Of these women, 560 (84.5%) consented to PM (572 stillborn infants) that was conducted according to the SCRN protocol. A standardized PM protocol was developed to evaluate stillbirth consistently across centers in the United States. Novel testing and approaches that increase the yield of the PM can be developed using this model.
Keywords: SCRN; postmortem examination; stillbirth; perinatal pathology